Invited article: a parallel process model of nonverbal communication. - Patterson, Miles L. (Journal of Nonverbal Behavior)
This article develops a parallel processing model of nonverbal communication that emphasizes the interdependence of behavioral and person perception processes from a functional perspective on social interaction. The form and outcome of the behavioral (encoding) and person perception (decoding) processes are a product of three related elements, including: (1) determinants, (2) the social environment, and (3) cognitive-affective mediators. In this model, the determinants (biology, culture, gender, and personality), in combination with the partner and setting, influence interpersonal expectancies, dispositions, goals, affect, and cognitive resources. In turn, these mediators constrain the attention and cognitive effort applied to behavior management and person perception. In general, fewer cognitive resources and decreased effort will have less effect on the outcome of automatic behavioral (e.g., scripts) and person perception (e.g., impressions based on appearance and nonverbal cues) processes than on more demanding ones. The utility of this theory in integrating behavioral and person perception processes into a single system is discussed. Reprinted by permission of the publisher.